Marine protected areas as a tool for environmental justice - Asokan, Anupa (Frontiers in Marine Science, 2024)
Overfishing, destructive industrial practices, and climate change are the biggest drivers of biodiversity loss in the ocean. Marine Protected Areas (MPAs), including through nature conservation initiatives like “30x30” and “America the Beautiful,” can be an effective solution to protect marine life and habitats, while making them more resilient to the pressures of extractive and destructive practices, as well as climate change impacts. There is general scientific consensus on the components that make MPAs ecologically effective, however, social context is often presented as burdensome—where protected spaces exclude communities from accessing nature. While this is a valid concern in top-down approaches to implementing protections around the world, under economic-driven systems of ocean management in countries like the United States, this narrative overlooks the potential opportunity of MPAs as a means to equity and environmental justice. In the U.S., the Magnuson-Stevens Fishery Conservation and Management Act (MSA) established a system that prioritizes the economic value of fisheries and centers power among Fishery Management Councils which are dominated by industry actors. Given this type of governance landscape, this perspective article presents MPAs as a step towards environmental justice in ocean management, whereby an MPA under the appropriate enabling conditions can be a tool to mitigate damage, distribute power, support other cultural value systems, and to advance our understanding of the ocean, climate change and diverse community impacts moving forward.